Potensi Ekstrak Daun Salam (Syzygium polyanthum) sebagai Pengawet Alami Ikan Kakap Merah (Lutjanus bitaeniatus) berbasis SDS-PAGE - Fitria, Meutia Srikandi; Nikmah, Khofifatun; Kartika, Aprilia Indra (Universitas Medan Area, 2025)
Red snapper is a source of animal protein with a highwater content so it is easily spoiled. Decay can be prevented by preservation such as natural and artificial preservatives. Natural preservatives can use natural ingredients such as bay leaves. Bay leaves can be used as a natural preservative because they contain antibacterial substances that can inhibit the growth of spoilage bacteria. The ability of bay leaves as a preservative can be seen with the SDS-PAGE method by looking at the protein profile. This study aims to determine the potential of bay leaf extract as a natural preservative in SDS-PAGE-based red snapper. This type of research is experimental based on the results of protein concentration, organoleptic test, and protein profile of SDS-PAGE results. There were 5 treatments of red snapper fish, namely fresh fish, fish without soaking stored 24 hours at room temperature, and fish with bay leaf extract with a concentration of 5%, 15%, and 25% for 30 minutes and then stored for 24 hours at room temperature. The results showed that the concentration of bay leaf extract that has the potential as a natural red snapper is 25%. This is because the protein concentration with this concentration is the highest (3.7226 µg/ µL), the best organoleptic test, and the SDS-PAGE results are almost the same protein band as the fresh control. This study concludes that bay leaf extract has the potential to be used as a natural preservative for red snapper with the highest concentration of protein.